2012
DOI: 10.1111/j.1463-1318.2011.02562.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and leptin are associated with adverse pathological features in male colorectal cancer patients

Abstract: We report a high prevalence of MetS and visceral obesity in a colorectal cancer population. MetS and plasma leptin are associated with a more aggressive tumour phenotype in male patients only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…In addition to increasing CRC risk, plasma leptin and leptin receptor levels have been associated with more aggressive tumour phenotype 104 144. An additional study of 108 Chinese patients with CRC reported a significant association between leptin/Ob-R expression and T and TNM staging, lymph node metastasis, distant metastasis, differentiation, and increased expression of phosphorylated PI3K, Akt and mTOR protein, suggesting that leptin may regulate the proliferation and apoptosis of CRC through the PI3K/Akt/mTOR signalling pathway 145.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to increasing CRC risk, plasma leptin and leptin receptor levels have been associated with more aggressive tumour phenotype 104 144. An additional study of 108 Chinese patients with CRC reported a significant association between leptin/Ob-R expression and T and TNM staging, lymph node metastasis, distant metastasis, differentiation, and increased expression of phosphorylated PI3K, Akt and mTOR protein, suggesting that leptin may regulate the proliferation and apoptosis of CRC through the PI3K/Akt/mTOR signalling pathway 145.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is well established that cancer cells undergo metabolic reprogramming to a glycolytic state to survive and maintain proliferation in a hostile environment and there is increasing evidence this warburg effect is promoted by oncogenes, including KRAS [53]. In CRC, leptin production has been associated with adverse outcome in male patients, associating with advanced disease, nodal status and venous invasion [54]. In another study, a metabolic gene signature able to predict patient's risk of relapse was shown to be associated with lower disease-free survival (HR 4.2 95% CI 1.79-9.88) [55].…”
Section: Phenotypic Characteristics -Metabolismmentioning
confidence: 99%
“…Stattin et al (2004) evidenced that an increasing level of leptin stimulates invasiveness of CRC in men, but not in women. Another study associated the aggressiveness of CRC tumor in male patients with high leptin levels and hypertension, raised plasma glucose, triglycerides, and high-density cholesterol levels (Healy et al, 2012). On the contrary, Ho et.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%
“…A growing body of evidence indicates that the metabolic syndrome (MetS) and expression of various adipokines (leptin and adiponectin) associated with obesity plays a crucial role in the development of colorectal cancer (Hardwick et al, 2001;Hoda et al, 2007;Endo et al, 2011;Aleksandrova et al, 2012;Healy et al, 2012;Erkasap et al, 2013;Gialamas et al, 2013). In obese people, the elevated insulin level, the rapidly growing secretion of leptin, and decreased adiponectin levels altogether activate several signaling pathways that favor carcinogenesis and are associated with colon cancer development.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%